Evaluation of the Population and Poverty Research Initiative (PopPov) - DaVanzo, Julie (RAND Corporation, 2014)
The RAND Corporation evaluated the Population and Poverty Research Initiative (PopPov) and its progress in achieving its goals of building and advancing the field of economic demography, orienting the work toward policy-relevant research, increasing economic policymakers' recognition of the value of lowering population growth rates and investing in family planning, and strengthening research capacity in sub-Saharan Africa.